(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the role and essence of a pragmatic approach to the problems of language and speech. Also the differences between the semantic, syntactic and pragmatic attitude in the process of speech acts are shown. In addition, it settles the difference between a pragmatic approach and style. The role of pragmatics in the disclosure of the identity in literary text is also emphasised.